Low rates of prescribing alcohol relapse prevention medicines in Australian Aboriginal Community Controlled Health Services ... - Purcell-Khodr, G; Conigrave, James; Lee, Kylie; Vnuk, J; Conigrave, KM (La Trobe, 2024)
Introduction: Alcohol dependence is a chronic condition impacting millions of individuals worldwide. Safe and effective medicines to reduce relapse can be prescribed by general practitioners but are underutilised in the general Australian population. Prescription rates of these medicines to Aboriginal and Torres Strait Islander (First Nations) Australians in primary care are unknown. We assess these medicines in Aboriginal Community Controlled Health Services and identify factors associated with prescription. Methods: Baseline data (spanning 12 months) were used from a cluster randomised trial involving 22 Aboriginal Community Controlled Health Services. We describe the proportion of First Nations patients aged 15+ who were prescribed a relapse prevention medicine: naltrexone, acamprosate or disulfiram. We explore associations between receiving a prescription, a patient AUDIT-C score and demographics (gender, age, service remoteness) using logistic regression. Results: During the 12-month period, 52,678 ...